2010
DOI: 10.1186/1471-2458-10-200
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness and cost effectiveness of adaptive e-Learning to improve dietary behaviour: protocol for a systematic review

Abstract: BackgroundThe composition of habitual diets is associated with adverse or protective effects on aspects of health. Consequently, UK public health policy strongly advocates dietary change for the improvement of population health and emphasises the importance of individual empowerment to improve health. A new and evolving area in the promotion of dietary behavioural change is e-Learning, the use of interactive electronic media to facilitate teaching and learning on a range of issues, including diet and health. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…During full‐text review of articles that included child and adolescent interventions (57 articles), 10 articles were excluded for the following reasons: Only one child study included in the article ( n = 5) 41,43–46 and did not present outcomes separately for children ( n = 5) 47–51 . Two protocols of retrieved studies ( n = 2) were identified 52,53 ; thus, this scoping review includes 47 papers of 45 reviews for the scoping analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During full‐text review of articles that included child and adolescent interventions (57 articles), 10 articles were excluded for the following reasons: Only one child study included in the article ( n = 5) 41,43–46 and did not present outcomes separately for children ( n = 5) 47–51 . Two protocols of retrieved studies ( n = 2) were identified 52,53 ; thus, this scoping review includes 47 papers of 45 reviews for the scoping analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible reviews were conducted to the AMSTAR 2 standard but did not report these components within their manuscript. For example, two articles reported using an adequate risk of bias tool in their published protocols for the review 52,53 but did not report this information within the actual systematic review or supplementary files 80,82 . In addition, it is likely that systematic reviews will have recorded excluded studies and reasons for exclusion during the conduct of their review but may not have reported these details in the publication.…”
Section: Discussionmentioning
confidence: 99%
“…The TDF is a theoretical framework for implementation research drawn from models to explain behaviour change. It was originally developed to identify psychological and organizational theory relevant to health practitioner behaviour change but has also been used to explain health‐related behaviour change among non‐health‐care professionals, including general population samples . At the time this study was designed, the framework covered a set of twelve domains comprising the main evidence‐based factors influencing behaviour change, such as beliefs about capabilities, social influences, knowledge and beliefs about consequences.…”
Section: Methodsmentioning
confidence: 99%
“…Two reports described questionnaire studies [ 13 , 14 ], and two reported both interviews and questionnaires [ 15 , 16 ]. There were four systematic reviews in which the theoretical domains were investigated as mediators of behaviour change [ 17 - 20 ], two randomised studies [ 21 , 22 ], and one protocol for a process evaluation study to explain trial effects in the context of a randomised trial [ 23 ]. The included studies provide evidence that the TDF has considerable breadth and cross-disciplinary impact in research about health-related behaviour (studies were published in 13 journals) and geographical reach (six countries from four continents were represented).…”
Section: Introductionmentioning
confidence: 99%